Association between duration to complete online assessment and student score among IIUM preclinical medical students - Mohd Noor, Mohd Fadly; Mat Harun, Noraihan; Wan Omar, Wan Fatein Nabeila; Mohd Radzuan, Hazulin; Ismail, Soraya; Abd. Rahim, Nour El Huda; Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Wahid, Hanan Hamimi; Ahmad Affandi, Khairunisa; Khaing, Aye Thi; et al. (2020)
Introduction: Following the COVID-19 pandemic, the International Islamic University Malaysia (IIUM) implemented an Emergency Remote Teaching and Learning (ERTL) to replace the conventional face to face teaching and learning method. The Innovative Teaching and Learning Environment System (iTa’LeEM), a Moodle-based learning platform has been imposed as an alternative method to evaluate the preclinical medical students. Although this platform is an official learning management system by IIUM, the server reliability and internet connectivity may influence the student performance.